Alejandra Pizarnik and the Poetics of Radical Incarnation. - Glover, Adam (Religion & the Arts, 2017)
Generally appreciated as one of the most original and creative voices in twentieth-century Latin American poetry, Alejandra Pizarnik (Argentina, 1936-1972) has not been regarded as a religious poet. Yet despite her explicit disavowal of all forms of religious commitment, Pizarnik's work is nonetheless animated by fundamentally theological concerns. This article examines in detail the theological motif of "incarnation" in Pizarnik's verse. It argues that, despite her avowed secularism, Pizarnik frames her own poetic project in explicitly incarnational language and that this theologically inflected vision underwrites her conception of poetic meaning-making.